Microruban Dipole Antenna for RFID Applications at 2.45 GHz - Loubna Berrich; Lahbib Zenkouar (Institute of Advanced Engineering and Science, 2016)
Radio Frequency Identification (RFID) is a technology used mainly to identify tagged items or to track their locations. The most used antennas for RFID application are planar dipoles. For antenna design, it is necessary that the antenna has an impedance value equal to the conjugate of the impedance of the integrated circuit CI. To have a good adaptation allowing the maximum power transfer, there are several techniques. In this work we focus to the adaptation technical T-match which is based on the insertion of a second folded dipole in the center of the first dipole. This technique is modeled by an equivalent circuit to calculate the size of the folded dipole to have new input impedance of the antenna equal to the conjugate of the impedance of the IC. We also look to present a conceptual and technological approach of new topologies of linear dipoles. We proceeded to fold at right angles of the radiating strands in order to explore other topologiesof type L and Z. The interest of this microstrip folded dipole is their effectiveness to achieve coverage of Blind directions. The results obtained by the platform Ansoft HFSS, allowed us to obtain a quasi-uniform radiation patterns and the reflection coefficients that exceed -37 dB.